2013
DOI: 10.1038/nature12865
|View full text |Cite
|
Sign up to set email alerts
|

p53 status determines the role of autophagy in pancreatic tumour development

Abstract: Macroautophagy (hereafter referred to as autophagy) is a process in which organelles termed autophagosomes deliver cytoplasmic constituents to lysosomes for degradation. Autophagy has a major role in cellular homeostasis and has been implicated in various forms of human disease. The role of autophagy in cancer seems to be complex, with reports indicating both pro-tumorigenic and tumour-suppressive roles. Here we show, in a humanized genetically-modified mouse model of pancreatic ductal adenocarcinoma (PDAC), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
596
6
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 624 publications
(658 citation statements)
references
References 32 publications
40
596
6
2
Order By: Relevance
“…26 In a separate study, it was also demonstrated that the loss of Atg5 or Atg7 could also prevent the development of high-grade pancreatic neoplastic legions induced by K-ras, and the pancreatic tumor growth could be restored if the expression of p53 was also abolished. 27 These recent findings together with ours indicate that autophagy is required for tumor progression for at least three different tumor types and that the deletion of p53 can partially restore tumorigenesis when autophagy is impaired.…”
Section: Discussionsupporting
confidence: 67%
“…26 In a separate study, it was also demonstrated that the loss of Atg5 or Atg7 could also prevent the development of high-grade pancreatic neoplastic legions induced by K-ras, and the pancreatic tumor growth could be restored if the expression of p53 was also abolished. 27 These recent findings together with ours indicate that autophagy is required for tumor progression for at least three different tumor types and that the deletion of p53 can partially restore tumorigenesis when autophagy is impaired.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, given observations of ER chemical chaperone-mediated resensitization of BRAF V600E melanoma cells to a panel of pro-apoptotic drugs, able to activate different apoptotic pathways, the use of drugs able to harness ER stress or, alternatively, to target the molecular pathways linking BRAF V600E -induced ER stress and basal autophagy (such as the IRE1/TRAF2/ASK1/JNK and the TRB3 axes) for the clinical benefit of such tumours is warranted. Observations demonstrating chloroquine/hydroxychloroquine can reduce tumour immunogenicity, 48 and accelerate tumour formation, 49 have questioned the benefit of autophagy inhibition in cancer therapy, and hence our novel proposed therapeutic approaches (ER stress buffering or JNK and TRB3 axes targeting) may also increase the sensitivity of BRAF mutant melanomas to clinical BRAF inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 BNIP3's contribution to tumorigenesis has yet to be linked to its role in mitophagy; however, the fact that increased levels of BNIP3 are associated with more aggressive disease suggests that a function in tumor cell survival via autophagy or mitophagy is a more likely mechanistic scenario than a role in cell death, in contexts of BNIP3 overexpression. Autophagy has documented roles in KRAS-driven lung 27,28 and pancreatic 40,41 cancer progression, and overactive RAS has been shown to upregulate BNIP3. 42 Further investigation of autophagy status in RAS-driven tumors with BNIP3 overexpression may reveal a mechanistic link between BNIP3 and tumor cell survival.…”
mentioning
confidence: 99%